Focus – The European Innovation Partnership creates a research strategy on water and agriculture - RICCOBONI, Pascale; RICCOBONI, Pascale (Sciences, Eaux & Territoires, 2020)
The European Innovation Partnership for Productive and Sustainable Agriculture (EIP-AGRI) is a European Union instrument for promoting innovation in agriculture by bringing research and field practice closer together. Pascale Riccoboni, in charge of the national implementation of EIP-AGRI within the National Rural Network, assesses this initiative and, the research strategy it has created in water and agriculture in France, and Europe.